Design, synthesis and conformational analysis of oligobenzanilides as multi-facial alpha-helix mimetics - Flack,T; Romain,C; White,A; Haycock,P; Barnard,A (Organic Letters, 2019)
The design, synthesis, and conformationalanalysis of an oligobenzanilide helix mimetic scaffold capableof simultaneous mimicry of two faces of an α-helix is reported.The synthetic methodology provides access to diversemonomer building blocks amenable to solid-phase assemblyin just four synthetic steps. The conformational flexibility ofmodel dimers was investigated using a combination of solidand solution state methodologies supplemented with DFTcalculations. The lack of noncovalent constraints allows forsignificant conformational plasticity in the scaffold, thuspermitting it to successfully mimic residues i, i+2, i+4, i+6, i+7, and i+9 of a canonical α-helix.